Eco-Anxiety and Environmental Education - Pihkala, Panu (Sustainability, 2020)
Anxiety and distress about the ecological crisis seems to be a rapidly growing phenomenon. This article analyzes the challenges and possibilities posed by such "eco-anxiety" for environmental education. Variations of eco-anxiety are analyzed, and it is argued that educators should be aware of the multiple forms that the phenomenon has. Eco-anxiety is found to be closely connected with many difficult emotions, such as grief, guilt, anger, and despair. However, anxiety also has an adaptive dimension, which can be called "practical anxiety". Anxiety is connected with expectation, motivation, and hopes. Previous research about eco-anxiety and ecological emotions in various disciplines is discussed, and related studies from various fields of education are brought together. Based on this extensive literature review, theoretical analyses are made, using a philosophical method. It is argued that environmental educators need organizational and peer support both in relation to their own difficult emotions and in order to develop emotional skills in their work. Educators should first practice self-reflection about eco-anxiety, after which they have many possibilities to help their audiences to develop emotional resilience. Potential practical activities related to eco-anxiety are discussed, drawing from various fields of education. These include validation of eco-anxiety and ecological emotions, providing safe spaces to discuss them, and, if possible, providing embodied and creative activities to more fully deliberate on them.